2019
DOI: 10.1136/bmjoq-2018-000602
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a standardised sign-up process to increase MyChart enrolment among HIV-positive patients

Abstract: Interactive patient portals are a valuable tool for engaging patients in their healthcare, with various functionalities including viewing laboratory results, refilling prescriptions and communicating directly with nurses, physicians and other healthcare providers via electronic messaging. The utility of patient portals is limited primarily from lack of patient uptake and enrolment due to a variety of factors including lack of awareness, low health literacy, poor technology mastery, lack of availability of a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…19 Another study by Sigler et al reported increased portal enrollment within an adult ambulatory HIV clinic of 6.4% over a 3-month period (54.8-61.2%). 20 Currently, the only study focusing on pediatric inpatient enrollment reported an absolute increase in activation from 9 to 26%. 21 Our patient portal enrollment percentage is higher than most previously published studies.…”
Section: Discussionmentioning
confidence: 99%
“…19 Another study by Sigler et al reported increased portal enrollment within an adult ambulatory HIV clinic of 6.4% over a 3-month period (54.8-61.2%). 20 Currently, the only study focusing on pediatric inpatient enrollment reported an absolute increase in activation from 9 to 26%. 21 Our patient portal enrollment percentage is higher than most previously published studies.…”
Section: Discussionmentioning
confidence: 99%